The Influence of The Saviter Learning Model on Student Learning Outcomes in Subtema 3 Ways to Maintain The Health of Human Blood Circulation Organs in Class V Sdn 091608 Sinaksak T.A 2023/2024 - Benardo Nainggolan; Rio Parsaoran Napitupulu; Masni Veronika Situmorang (MultiTech Publisher, 2023)
Savi learning model on student learning outcomes in subtheme 3 ways to maintain the health of human circulatory organs in class V SDN 091608 Sinaksak T.A 2023/2024. The type of research in this research is quantitative, the research population is all class V students at SDN 091608 Sinaksak totaling 30 students. The sampling technique used saturated samples, the sample in this study consisted of all class V of SDN 091608 Sinaksak, totaling 30 students. The research results show that student learning outcomes using the Savi model are in the good category with an average of 77.6. The results of the t distribution test are at a significant level ( α = 0.05) and dk = N–1=30-1=29, namely t count > t table , so the t distribution data with results is 18.525 > t table 2.045, so it can be said that there is a significant influence . The results of the t test table prove that there is an influence of the Savi learning model (x) on learning outcomes (Y) with the results of r calculated > r table with the results of t calculated > t table 18.525 > 2.045, so Ho is rejected and Ha is accepted. This proves that there is a significant influence from the use of the Savi learning model on student learning outcomes in sub-theme 3 ways to maintain the health of human circulatory organs in class V SDN 091608 Sinaksak T.A 2023/2024.